PENGARUH PEMBANGUNAN INFRASTRUKTUR TERHADAP PERTUMBUHAN EKONOMI PROVINSI SUMATERA BARAT - Patria Nagara; Dheya Vortuna; Novi Yanti; Zusmawati (Universitas Sumatera Barat, 2021)
The provision of infrastructure is very important in the stage of development. Infrastructure contributes to the regional economy and makes economic development more increased by giving direct and indirect effects. But still quite a lot of problems experienced in infrastructure develompment, one of which is the imbalance of development between regions. The purposes of this study was to explain and analyze the influence of infrastructure development to economic growth in West Sumatera Province especially road infrastructure, electricity infrastructure and seaport infrastructure. The research analysis used in this study is descriptive and quantitative analysis model with multiple regression method which used data in the period of 2004-2018. Variables that are used in this study is Gross Domestic Regional Product (GDRP) as the output measurement, length of road (km), sum of electricity production and consumption (MWh), and sum of seaport loading and unloading volumes (ton). Based on the model in analysis, road infrastructure has no effect to the economic growth in West Sumatera Province. While electricity infrastructure and seaport infrastructure affect to the economic growth in West Sumatera Province. In the resaerch results, seaport infrastructure give the highest contribution to the economic growth in West Sumatera Province. From the regression results, the value of R-Square (R2) is 0,745. This means that the independent variables is able to explain the dependent variable 74,5% while the remaining 25,5% is explained by other variables outside the model.